Inisiasi Pengolahan Air Embung dengan Teknologi Multimedia Filter (MMF) sebagai Solusi Air Bersih di Kabupaten Bojonegoro - Chusnul Arif; Allen Kurniawan; Endang Warsiki; Teuku Devan Assiddiqi; Ahmad Rijani Hasby (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Clean water and proper sanitation are fundamental human needs. Nganti Village, located in Ngraho Subdistrict, Bojonegoro Regency, faces significant drought and clean water shortages, particularly during the dry season. The water quality remains subpar despite the presence of springs and water reservoirs. Consequently, processing raw water from the village's reservoir can offer a viable solution. This service activity aims to harness water reservoirs as a clean water source through multimedia filter (MMF) technology. The activities, conducted from 2022 to the end of 2023, encompass four stages: socializing the program plans, constructing multimedia filters (MMF), installing the water treatment unit on-site, and evaluating water quality, followed by necessary follow-ups. The primary activities involve installing water treatment units with MMF technology in collaboration with village officials and the community. The treated water is then tested for quality at the IPB University laboratory. Test results indicate that MMF technology significantly improves water quality, reducing parameters such as Magnesium, Manganese, Calcium, Iron, and Phosphate by 25.8‒97.8%, thus meeting quality standards. However, some parameters, such as TSS, COD, and Zinc, still exceed quality standards, necessitating further processing. This advanced water treatment requires involvement from the local government, particularly in funding through community empowerment programs, to install advanced treatment units and provide operational support for these units.